MINAT SISWA TERHADAP PEMBELAJARAN SENI TARI KELAS VIII MTsN PEKAN SELASA KABUPATEN SOLOK SELATAN - Elfi Yulianti; Zora Iriani; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2012)
The purpose of research is to know and to description about student interest to lesson dance of art an MTsn Pakan Selasa Regency of South Solok. The kind of research that do is quantitative and descriptive and to use questionnaire technic. Indicator that to use is attention feeling and discipline. Analyze data to base of result a research to show that student interest to lesson dance of art at MTsN Pekan Selasa Regency of South Solok. That have to category is very good or 91,7% (Attention Indicator, 87,23%, Feeleng indikator 83,14%, dicipline indikator 104,75%).